DRIVING SUSTAINABLE DEVELOPMENT GOALS THROUGH SOCIAL ENTREPRENEURSHIP AND INNOVATION: A CASE STUDY OF MALAYSIA - Siti Shalima Sabri; Siti Asma Mohd Rosdi @ Mohd Rodhi (Jurnal Penyelidikan Sains Sosial, 2023)
The present study aims to examine the interconnections among social entrepreneurship, innovation, and the attainment of sustainable development goals (SDGs) within the context of Malaysia. This study conducts an analysis of illustrative instances and empirical investigations to explore the ways in which social enterprises in Malaysia make contributions towards diverse Sustainable Development Goals (SDGs), including poverty alleviation, enhancement of educational quality, promotion of gender equality, and fostering economic growth. This paper emphasizes the significance of innovation in propelling social entrepreneurship endeavours and cultivating sustainable development strategies. Furthermore, we aim to examine the influence of innovation in effectively tackling the various challenges associated with sustainable cities, responsible consumption, climate action, and partnerships for achieving the goals. This study emphasizes the significance of collaboration, knowledge dissemination, and partnerships across different sectors in the pursuit of Sustainable Development Goals (SDGs) through social entrepreneurship and innovation. The results of this study enhance comprehension regarding the dynamic relationship among social entrepreneurship, innovation, and sustainable development within the specific context of Malaysia. These findings provide valuable knowledge for policymakers, practitioners, and researchers.